Pemaknaan Pesan Kesetaraan Gender dalam Femvertising pada Penonton Laki-laki Etnis Betawi - Isti Purwi Tyas Utami; Ina Nurfika Putri (STARKI, 2023)
Gender equality is still a minority message in the Indonesian advertising industry which tends to be male centric. Femvertising as a form of correction to commodity feminism is still relatively new amid advertising audiences that are strongly influenced by patriarchal culture. In general, femvertising in Indonesia presents women as the main endorsers who carry messages of equality and empowerment. It is rare to find femvertising which displays men in the domestic area and does work that is identical to women's. GoPay, Arisan Mapan and Kecap ABC advertisements are three advertisements that dare to use the slice of life message approach by featuring male endorsers doing domestic work. Advertising messages that portray realities related to gender and roles in the domestic sphere can be interpreted in various ways by advertising audiences in a patriarchal society. One of the ethnic groups closely related to patriarchal culture is the Betawi ethnic group. This study aims to find out how the Betawi ethnic male audience interprets the message of gender equality in femvertising. The study used a constructivist paradigm with qualitative research and reception analysis methods from Stuart Hall. The results of the study involving five Betawi ethnic male informants aged early adulthood and married showed that there were three dominant positions and two negotiation positions. The most influential contextual factor in the meaning of messages is the socialization of family values. The Betawi ethnic factor, which is synonymous with patriarchal traditions, does not affect the acceptance of gender equality messages by informants. Abstrak Kesetaraan gender masih menjadi pesan minoritas dalam industri iklan Indonesia yang cenderung male centric. Femvertising sebagai bentuk koreksi terhadap commodity feminism pun masih terhitung baru di tengah khalayak iklan yang kuat dipengaruhi oleh budaya patriarki. Pada umumnya femvertising di Indonesia menampilkan perempuan sebagai endorser utama yang membawa pesan kesetaraan dan pemberdayaan. Jarang didapati femvertising yang menampilkan laki-laki di wilayah domestik dan melakukan pekerjaan yang identik dengan perempuan. Iklan GoPay, Arisan Mapan dan Kecap ABC adalah tiga iklan yang berani menggunakan pendekatan pesan slice of life dengan menampilkan endorser laki-laki yang melakukan pekerjaan domestik. Pesan iklan yang memotret realitas terkait gender dan peran di wilayah domestik dapat dimaknai secara beragam oleh khalayak iklan dalam masyarakat patriarkal. Salah satu kelompok etnis yang lekat dengan budaya patriarkal adalah etnis Betawi. Penelitian ini bertujuan mengetahui bagaimana pemaknaan penonton laki-laki etnis Betawi pada pesan kesetaraan gender dalam femvertising. Penelitian menggunakan paradigma konstruktivis dengan jenis penelitian kualitatif dan metode analisis resepsi dari Stuart Hall. Hasil penelitian yang melibatkan lima informan laki-laki etnis Betawi berusia dewasa awal dan telah menikah menunjukkan terdapat tiga posisi pemaknaan dominan dan dua posisi pemaknaan negosiasi. Faktor kontekstual yang paling berpengaruh dalam pemaknaan adalah sosialiasi nilai-nilai dalam keluarga. Faktor etnis Betawi yang identik dengan tradisi patriarkal tidak memengaruhi penerimaan pesan kesetaraan gender pada informan.